An Efficient Route for Electrooxidation of Methanol to Dimethoxymethane Using Ionic Liquid as Electrolyte. Issue 8 (5th May 2017) - Li, Ying; Wang, Hongmei; Wang, Hongxia; Lu, Bin; Zhao, Jingxiang; Cai, Qinghai
Abstract : An ionic liquid 1-ethyl-3-methyl imidazolium tetrafloroborate (EmimBF4 ) was found to be highly active for one-pot synthesis of dimethoxymethane (DMM) by electrooxidation of methanol on platinum electrode, exhibiting 34.7% conversion, 96.9% selectivity to DMM, high current efficiency (99.2%) as well. The electrode reaction mechanism was proposed according to the experimental results and reported literature.